Temporary Foreign Workers and Firms: Theory and Canadian Evidence - Pierre Brochu; Till Gross; Christopher Worswick (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2016)
The goal of our paper is to better understand the economic implications of Temporary Foreign Worker (TFW) programs as well as comprehend the underlying reasons for the rapid expansion of the number of TFWs hired by employers under the Canadian program brought to light in 2014. We present an efficiency wage model that allows for the possibility that a firm, unable to find a worker after advertising for a period of time, may hire a TFW at the advertised wage. Due to the assumed lower outside option for the TFW than the domestic worker, the TFW will exert higher effort than a domestic worker even if the TFW is paid the same wage as would have been paid to a domestic worker. In equilibrium, lower wage o ers are made to less-skilled domestic workers when a TFW program of this kind is in place. The model also implies higher unemployment rates for domestic workers after the introduction of a TFW program. Our empirical analysis is based on the confidential master files of the Canadian Census (1991-2006) and the Labor Force survey (2006-2013). We find that TFWs in Canada work longer hours, have lower rates of absenteeism, and are less likely to be laid off, consistent with higher effort in our model. Moreover, TFWs work at lower wage rates than domestic workers even for similar job characteristics, which is also a prediction of our model.
Keywords: J15; J24; J31; J61; J62; J71; 330; temporary foreign workers; guest workers; efficiency wage; hours; wages; absenteeism; job transitions